(3GdCOhjI GdeaQOIs - (3CHh LYaQ CMeO Hf eMeO Hf eMeO GdeYQha HGHf CHi GdCTYK,J (B365 (3g` s
(3ChdgG (B:s
(3HGH GdPGd PgH bGd Mfjf (B: (3GdPgH ai ZGjI GdGYJOGd , jfaY ef hLY GdbdH GdeRef hjVQ HGdeKGfI , hjUdM HGdYSd hGdeSc s
(3BNQgG (B:s
(3hdbO fbdJg Ydi CMTGFi afaYfi , hCeG eJi TO Ydi eYOI (B( (3ef (B) (3jYQV dg GdUQY , hcGf ef eYOJg , TaGg dG eMGdI s
(3HChdgG hBNQgG Jedc HGSe eMeO Hf CMeO GdfTQJi ` GdcMGd HOGQ GdTaGA HeUQs
(3SfI (B1045 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B201s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B8 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs